Studi Literatur: Kebutuhan Pelayanan Kesehatan yang Belum Terpenuhi pada Penyintas Kanker Ginekologi - Sely Kresna Dewi; Marghareta Martini (Jurnal Kesehatan Manarang, 2021)
There is an urgent increase of health care needs for cancer survivor nowadays caused by the escalations of global cancer survivor’s unmet need for cancer care health services. The purpose of this literature study was to identify the gynecology cancer survivor’s unmet need of health care services. A literature search was PRISMA for relevant research paper. Six database were searched: Proquest, Elsevier, Spinger, Wiley Online Library, and Google Scholar using keyword: “CaSUN”, “SCNS-SF34”, “Unmet need”,” Survivor cancer”, “Supportive care”, Cancer Gynecological”. The final review included 9 articles from 993 article that being identified from 2015 – 2020. The result of this study was minimum 1 unmet need found in every gynecology cancer survivor, psychological needs and information on health services, physical and sexual needs.